(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims at providing a better knowledge of Competitor Intelligence tools & techniques. “CHANGES REMAINS UNCHANGED “is a powerful eye-opener key tool. Since when world becomes Digitalized the marketing research also turned into digital form. A common customer never thinks that how our desired product Avails in the market. But the modern marketer could able to read their customer mind without approaching them directly.. for this magical result one corporate company is reading & observing their rival competitor. This article based on an empirical study of Competitor intelligence tools & techniques strategies towards FMCG marketers of India